2020
DOI: 10.1002/essoar.10504552.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Venus' Mass Spectra Show Signs of Disequilibria in the Middle Clouds

Abstract: Venus' clouds harbor several proposed trace chemical species that suggest the potential for chemistries yet to be discovered. Exemplar trace species include ammonia, oxygen, hydrogen, methane, and ethene, which were detected remotely or in situ (

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A fundamental requirement for life is a source of free energy [ 1 ]. Redox gradients may be available as energy sources in the clouds of Venus [ 110 ], but light to power photosynthesis is the most abundant energy source. We note that CSA is capable of supporting photochemical interconversion of other transition metal complexes (e.g., Re(VIII)/Re(VI) [ 111 , 112 ]).…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental requirement for life is a source of free energy [ 1 ]. Redox gradients may be available as energy sources in the clouds of Venus [ 110 ], but light to power photosynthesis is the most abundant energy source. We note that CSA is capable of supporting photochemical interconversion of other transition metal complexes (e.g., Re(VIII)/Re(VI) [ 111 , 112 ]).…”
Section: Discussionmentioning
confidence: 99%
“…All the metabolisms required reduced species as input, either hydrogen-containing compounds (H 2 S or H 2 ) or carbon monoxide. Reduced compounds are predicted to be rare in Venus' oxidized atmosphere (e.g., Marcq et al, 2018), and the limited experimental data confirm this (e.g., Mogul et al, 2021b;, so it is not surprising that the chosen metabolisms could not explain the SO 2 depletion. Interestingly, Jordan et al found that the chemical energy available could support a biosphere within the mass ranges summarized in Table 1.…”
Section: Energymentioning
confidence: 99%
“…T he tentative detection of phosphine in the atmosphere of Venus (Bains et al, 2021b(Bains et al, , 2022aGreaves et al, 2021aGreaves et al, , 2021bGreaves et al, , 2021cGreaves et al, , 2022Mogul et al, 2021b) has re-ignited interest in the idea that life might exist in Venus' clouds. With that renewed interest have come a variety of suggestions that what we know about Venus inherently rules out the possibility of life, and consequently that investing effort in modeling or detecting Venusian life is a waste of resources at best, unscientific at worst (Cockell et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Especially insightful would be if a different methodology could be employed, such as trying to detect phosphine in the infrared range of the spectrum. An independent confirmation could also derive from a re-analysis of the Large Probe Neutral Mass Spectrometer (LNMS) on board of the Pioneer-Venus mission, as done by Mogul et al [ 52 ]. In their recently published paper, they claimed that their analysis is suggestive of PH 3 and H 2 S being present in the middle clouds, based on a peak fitting model that uses data points within the LNMS dataset to estimate the full-width half-maximum and peak heights of chemical reference and target species.…”
Section: The Claimed Detection Of Phosphinementioning
confidence: 99%